Rancang Bangun Peringatan Terjadinya Potensi Kebakaran pada Box Panel Kapal Container Berbasis Microcontroller Atmega 328 - Dimas Satria Abdullah; Agus Dwi Santoso; Dwi Yanti Margosetiyowati (Pusat Riset dan Inovasi Nasional, 2024)
Arduino is an electronic kit or open source electronic circuit board which contains the main component, namely a microcontroller chip with the AVR (Alf and Vegard's Risc Processor) type from the Atmel company (Lulu F., et al, 2018 and Setyowinoto et al, 2017). From this research it can be seen how to prevent potential fires on ship box panels, by using an ATMEGA328 microcontroller which can be commanded by a fire sensor or fire sensor and DHT22 temperature and humidity sensor to monitor the ship box panel, which if a fire occurs will be detected directly by The two sensors will send a command to the buzzer and then sound, and the LCD will display information about whether a fire has been detected. In this research, researchers used qualitative research and R&D to understand phenomena in a natural social context. In qualitative research, the researcher analyzes and after that reports the phenomenon in the results of the analysis in the research. Qualitative methods are research to describe and analyze phenomena, events, beliefs, attitudes and social activities individually and in groups. Research and Development (R&D) research method is a research method used to produce certain products and test the effectiveness of these products. From the results of this research, it was found that the temperature and humidity sensor, namely DHT22, can experience changes in temperature and humidity when placed close to a hot tool or medium, with an initial humidity temperature of 61.10% - 62.50% and an initial temperature of 31.90 degrees Celsius, experiencing a drastic change. the humidity temperature figure from the initial 62.50% decreased to 36.80% and the temperature which was initially estimated at 31.90 degrees Celsius rose to 43 degrees Celsius when the soldering tool was very close. Then the fire sensor or Flame Sensor, which if there is no fire, will appear on the LCD screen with the statement